Spatio-temporal Characteristics of Coupling Coordination Between Rural Revitalization and Sustainable Land Use in China During 2010—2019 - Li Bing; Zhou Xing; Chen Haiping (Shuitu baochi tongbao)
[Objective] The spatio-temporal characteristics and aggregation degree of the coupling coordination between rural revitalization and sustainable land use in China from 2010 to 2019 were analyzed in order to provide a basis for promoting the completion of the rural revitalization strategy, improving rural prosperity, and maintaining sustainable land use. [Methods] An index system was constructed based on 31 provinces in China. The coupling degree and coordination degree model and spatial autocorrelation model method were used to analyze the data. [Results] ① The horizontal spatial distribution of rural revitalization and sustainable land use in China decreased from east to west. The regional gap between provinces decreased. ② The coupling coordination values were mainly between 0.6 and 0.7, belonging to primary coordination. The spatial distribution was characterized as being “strong in the east and weak in the west”, and a trend of striping pursuit in the west, central, and east was obvious. ③ Global Moran's I index was positive (0.484 4~0.566 4), and the local aggregation characteristics were gradually prominent. The distribution was dominated by the high-high aggregation type in the east, and by the low-low aggregation type in the west. [Conclusion] There were significant regional differences in the level of coupling coordination between rural revitalization and sustainable land use in China. In the future, in response to the regional orientation of accelerating the modernization of the eastern part of the country, the revitalization of the northeast, the rise of the central region, and the development of the west, the development and interaction between regions should simultaneously be strengthened, the radiation-driven effect of the eastern region should be increased, and the development level of the western, central, and northeastern regions should be enhanced.